On the Cauchy problem for two-dimensional systems of linear functional differential equations with monotone operator - Šremr, J.; Hakl, R. (Нелінійні коливання, 2007)
We establish new efficient conditions sufficient for the unique solvability of the Cauchy problem for twodimensional systems of linear functional differential equations with monotone operators. Знайдено новi ефективнi умови, що є достатнiми для iснування єдиного розв’язку задачi Кошi
для двовимiрних систем лiнiйних функцiонально-диференцiальних рiвнянь з монотонними операторами.